Developing Effective Marketing Strategies for A New MRO Company: A Case Study of Akasa Teknologi Nusantara at Soekarno-Hatta International Airport - Mahardhika Rizky Gumarianto (PT. Publikasiku Academic Solution, 2025)
The aviation Maintenance, Repair, and Overhaul (MRO) industry is an important pillar in ensuring aircraft safety, operational efficiency, and regulatory compliance. This study aims to analyze the internal and external factors that influence Akasa Teknologi Nusantara in marketing their services in the MRO industry in Indonesia. This study uses data triangulation, integrating qualitative data collected through interviews as primary data, supported by statistical data collected through the Directorate General of Civil Aviation (DGCA) that validates the interview results. A thorough and comprehensive evaluation using strategic marketing formulation through analysis of PESTEL analysis framework, Porter's Five Forces, B2B Value Pyramid, and VRIO analysis to provide a holistic perspective of ATN's competitive landscape as a new entrant in the industry. In addition, STP (Segmentation, Targeting, and Positioning), 7P Marketing Mix, and Five Product Levels analysis to analyze and formulate a market entry strategy for ATN's value proposition. Safety and compliance remain of utmost importance for any aviation-related company, including ATN as an MRO service provider, as airline clients prioritize partners that meet strict aviation safety standards and certification requirements to demonstrate their compliance with regulations. The implementation plan to increase such value can be done through SEO-optimized websites and social media engagement to increase brand and industry awareness, as well as participating in aviation industry exhibitions and conventions to increase brand recognition.